Alocação Otimizada de Centrais Solares Fotovoltaicas no Sistema de Distribuição do Oeste do Estado da Paraíba - Paes Junior, Marcelo Renato de Cerqueira (2014)
The present work aims to simulate the effects of connecting photovoltaic power plants in the active energy losses of the distribution system at the west of the state of Paraíba. Initially was done the modeling of the distribution system, which has one supply point, 20 substations 69/13.8 kV and 25 distribution lines 69 kV. For network analysis was used the Newton-Raphson method for solution of power flow after and before the insertion of photovoltaic plants and finally an optimized allocation of solar photovoltaic plants has been proposed with the aim of minimizing losses of active power using genetic algorithms.